Pengaruh Bauran Pemasaran Media Instagram Terhadap Keputusan Pembelian Kue Ulang Tahun Custom Bicoco - Putri Syifa Nurkhasanah; Beta Asteria (Jurnal Manajemen DIVERSIFIKASI, 2025)
Analyzing the influence of Instagram's media marketing mix on decisions to buy Bicoco personalized birthday cakes was the purpose of this research. Research of this type uses a quantitative approach. Customers who bought personalized birthday cakes from Bicoco made up the study's target audience. The sampling strategy used was a combination of purposive and 88 respondents made up the sample size for non-probability sampling. The questionnaire, which was further utilized to gather data and was examined for validity and reliability. Multiple linear regression analysis was employed as the data analysis method in this investigation. The link between independent and dependent variables was examined using this methodology. According to the study's findings, distribution has a positive impact on decisions to buy, advertising has a positive impact, price has a negative impact, and the product has a positive influence. With an R2 the worth of 0.745, this is study demonstrated that the variables of product, price, advertising, and distribution could account for 74.5% of the factors impacting purchase decisions, with the remaining 25.5% coming from factors not covered in the study